Unveiling the pathogenic mechanisms of Clostridium perfringens toxins and virulence factors - Anny Camargo; Juan David Ramírez; Raymond Kiu; Lindsay J. Hall; Marina Muñoz (Emerging Microbes and Infections, 2024)
Clostridium perfringens causes multiple diseases in humans and animals. Its pathogenic effect is supported by a broad and heterogeneous arsenal of toxins and other virulence factors associated with a specific host tropism. Molecular approaches have indicated that most C. perfringens toxins produce membrane pores, leading to osmotic cell disruption and apoptosis. However, identifying mechanisms involved in cell tropism and selective toxicity effects should be studied more. The differential presence and polymorphisms of toxin-encoding genes and genes encoding other virulence factors suggest that molecular mechanisms might exist associated with host preference, receptor binding, and impact on the host; however, this information has not been reviewed in detail. Therefore, this review aims to clarify the current state of knowledge on the structural features and mechanisms of action of the major toxins and virulence factors of C. perfringens and discuss the impact of genetic diversity of toxinotypes in tropism for several hosts.